International Electron Devices Meeting 2000. Technical Digest. IEDM (Cat. No.00CH37138)
DOI: 10.1109/iedm.2000.904375
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent voltage-acceleration of oxide breakdown for ultra-thin oxides

Abstract: We report the voltage-dependence of voltage acceleration for ultra-thin oxides from 2.2V to 5V over a range of Tox values from 1.7nm to 5.0 nm. This unique behavior manifest itself as a power-law voltage-dependence for time-to-breakdown (TBD) over a variety of experimental observations. Using the concept of energy-to-breakdown, we explore the possible scenarios such as fractional energy or defect generation probability as a function of voltage to account for the increase in voltage acceleration with decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 5 publications
2
30
0
Order By: Relevance
“…21) with c $ 7.5 for 5 nm thick films but asymptoting to lower values for thicker films. 22 This similarity suggests that the mechanism causing a change in the resistive state in an oxide-based RRAM is likely to arise from a breakdown mechanism ameliorated by the limiting resistance of the polymer layer, i.e., a form of soft breakdown. The results in Fig.…”
Section: B Transient Response In the On-statementioning
confidence: 99%
“…21) with c $ 7.5 for 5 nm thick films but asymptoting to lower values for thicker films. 22 This similarity suggests that the mechanism causing a change in the resistive state in an oxide-based RRAM is likely to arise from a breakdown mechanism ameliorated by the limiting resistance of the polymer layer, i.e., a form of soft breakdown. The results in Fig.…”
Section: B Transient Response In the On-statementioning
confidence: 99%
“…The thinner oxides (1.4-1.6 nm) appear to exhibit a larger voltage acceleration. It was later realized that the voltage acceleration parameter was a function of voltage not oxide thickness [40], [75]. Thinner oxides are tested at lower voltages than thicker oxides.…”
Section: B Voltage and Temperature Accelerationmentioning
confidence: 99%
“…The larger voltage acceleration at lower voltages was explained as an increased energy-to-breakdown since dissipated energy required for the production of oxide defects decreases dramatically at low voltages [75]. The larger voltage acceleration parameter may also be a consequence of a larger or a smaller defect generation rate at lower voltages [67].…”
Section: B Voltage and Temperature Accelerationmentioning
confidence: 99%
See 1 more Smart Citation
“…7 for n-and p-MOSFETs, respectively. For a thicker oxide tox=130 Å and same area, it is observed that the oxide lifetime and β values increase compared to the thinner oxide [34]- [35], as depicted in Fig. 9.…”
Section: Statistical Gate Oxide Evaluation Under Vftlp and Discussionmentioning
confidence: 99%